Pembuatan Sarana Air Bersih Sumur Gali di Wilayah Kerja Puskesmas Palolo Kabupaten Sigi: Construction of Dug Well Clean Water Facilities in the Work Area of the Palolo Health Center, Sigi Regency - Hanum Sasmita; Amsal Amsal; Novarianti Novarianti (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
Humans need water as a necessity for life, they must meet various requirements in quality, quantity, and continuity. Dug wells are clean water facilities that are widely used by the community, both in urban and rural areas because dug wells are relatively easy and inexpensive to manufacture. The purpose of this activity was to procure pilot dug wells and increase public knowledge about dug wells that meet health requirements in the work area of ​​the Palolo Health Center, especially in Rahmat Village. The method used was a combination of lecture, discussion, and practice methods. The target was the community in Rahmat Village whose dug wells do not meet the requirements and conducted pilot construction of 1 dug well. The results of community service can be seen from the dug wells that have been made as pilots and the achievement of goals can be said to be good seen from the level of understanding and activeness of the participants in discussions and sharing information with other participants. The achievement of the material targets was good and seen from all the training materials delivered by the community service team. Suggestions, with the addition of one dug well unit, it is hoped that the community can maintain and maintain clean water facilities and increase public awareness of the importance of making dug wells that meet the requirements to improve health status. ABSTRAK Manusia membutuhkan air sebagai kebutuhan hidupnya harus memenuhi berbagai persyaratan, terutama kualitas, kuantitas dan kontinuitas. Sumur gali merupakan sarana air bersih yang banyak digunakan masyarakat, baik di perkotaan maupun di pedesaan karena sumur gali tergolong mudah dan murah pembuatannya. Tujuan pengadaan sumur gali percontohan serta bertambahnya pengetahuan masyarakat tentang sumur gali yang memenuhi persyaratan kesehatan di wilayah kerja Puskesmas Palolo khususnya di Desa Rahmat. Metode yang digunakan dalam kegiatan ini adalah penggabungan metode ceramah, diskusi dan praktik. Sasaran adalah masyarakat di Desa Rahmat yang sumur galinya belum memenuhi syarat dan melakukan pembuatan percontohan sumur gali sebanyak 1 buah. Hasil dari pengabdian masyarakat dapat dilihat dari telah dibuatnya sumur gali sebagai percontohan dan ketercapaian tujuan dapat dikatakan baik dilihat dari tingkat pemahaman dan keaktifan para peserta dalam diskusi dan berbagi informasi dengan peserta lainnya. Ketercapaian target materi dapat dikatakan baik dilihat dari semua materi pelatihan yang disampaikan oleh tim pengabdian kepada masyarakat. Saran, dengan adanya penambahan satu unit sumur gali, diharapkan masyarakat dapat menjaga dan memelihara sarana air bersih sumur gali serta adanya peningkatan kesadaran masyarakat akan pentingnya pembuatan sumur gali yang memenuhi persyaratan sehingga dapat meningkatkan derajat kesehatan.